Contribution of close-in fallout from the French atmospheric tests in inventories of 137Cs, 241Am and plutonium (238, 239, 240) in Gambier Islands (French Polynesia) – Signatures of stratospheric fallout in the Southern Hemisphere. (September 2021) - Bouisset, P.; Nohl, M.; Cossonnet, C.; Boulet, B.; Thomas, S.; Cariou, N.; Salaun, G.
Abstract: The inventories of 137 Cs (503 ± 34 Bq.m −2 ), 241 Am (11.3 ± 1.2 Bq.m −2 ), 241 Pu (33.7 ± 3.4 Bq.m −2 ), 238 Pu (6.82 ± 0.87 Bq.m −2 ) and 239+240 Pu (113.0 ± 5.9 Bq.m −2 ), sum of 239 Pu (100 ± 11 Bq.m −2 ) and 240 Pu (14.5 ± 1.7 Bq.m −2 ), in the Gambier archipelago (23°S) of the French Polynesia, are well higher the global fallout at this latitude, in unequal proportions for the different radionuclides. ( 240 Pu/ 239 Pu)AR (AR: atomic ratio) of 0.0394 ± 0.0062, and ( 241 Pu/ 239 Pu)AR of (2.03 ± 0.39)10 −4, confirm that the overwhelmingly dominant source of these radionuclides comes from local fallout during the 1970s of the French atmospheric tests of Moruroa and Fangataufa located nearly 400 km from Gambier. The signatures of the local fallout were deduced from the excess of its inventory in 137 Cs and from the mixing lines established from the signatures of the global fallout, some of the test sites and the isotopic ratios measured in Gambier. Signatures obtained are 2.0 ± 0.4 for 137 Cs/ 239+240 Pu, 0.045 ± 0.008 for 238 Pu/ 239+240 Pu, 0.031 ± 0.009 for 241 Am/ 239+240 Pu, 0.092 ± 0.027 for 241 Pu/ 239+240 Pu, 0.0163 ± 0.0049 for ( 240 Pu/ 239 Pu)AR, (0.78 ± 0.23)10 −4 for ( 241 Pu/ 239 Pu)AR . The concordance of the mixing lines of the [( 240 Pu/ 239 Pu)AR, ( 241 Pu/ 239 Pu)AR ] and the linear regression of these ratios measured in the stratosphere (40°S) during the 1970s, indicates that the signatures of the close-in deposition are also those of the stratospheric injections of the French tests. The signatures of stratospheric fallout in the Southern Hemisphere were evaluated by considering that the fission energy of these injections represents 11% and that of the Northern Hemisphere represents 89% and that the isotopic ratios of stratospheric injections remained the same over the period 1970–1974. The activity ratios deducted are 21.9 ± 0.1 in 137 Cs/ 239+240 Pu, 0.11 ± 0.05 in 238 Pu/ 239+240 Pu, 1.03 ± 0.12 in 241 Pu/ 239+240 Pu and 0.35 ± 0.04 in 241 Am/ 239+240 Pu. The associated atom ratios are 0.157 ± 0.011 for ( 240 Pu/ 239 Pu)AR and (8.33 ± 0.48)10 −4 for ( 241 Pu/ 239 Pu)AR . These signatures appear to be consistent with the results of the inventories at Hiva Oa, located more than 1, 000 km north of both French test sites, and with those found in the Australian continent, in regions not impacted by UK-test debris. The proportions of close-in tropospheric fallout from the French tests are about 90% in Gambier. They represent a proportion in the inventories of 40% for the 137 Cs, 60% for 241 Am and in the range between 80 and 90% for Pu isotopes. Highlights: Radioisotope inventories in Gambier are well higher than global fallout. Activity and atom ratios clearly show close-in fallout from French test sites. Signatures of close-in fallout are established. Signatures of stratospheric fallout in Southern Hemisphere are proposed.